1985
DOI: 10.1177/030089168507100212
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide, Adriamycin and Platinum (CAP) Combination Chemotherapy, A New Effective Approach in the Treatment of Disseminated Breast Cancer. Preliminary Report

Abstract: The prospective controlled Phase III clinical trial tested the therapeutic value of the cis-platinum-adriamycin-cyclophosphamide combination (CAP), compared with the combination including cyclophosphamide, methotrexate, 5-fluorouracil, vincristine and prednisolone (CMFVP), in untreated metastatic breast cancer. One hundred and twenty-three patients (greater than 2 cycles) were evaluated: 61 on the CAP, and 62 on the CMFVP schedule. An objective response (CR + PR) to CAP combination chemotherapy was achieved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Cependant, quelques études ont montré une efficacité notable en première ligne de traitement, parfois supérieure aux traitements de référence. Ainsi, dans une étude publiée en 1985 [10], il était montré que l'association CDDP/Doxo/CPM chez des patientes métastatiques en 1 re ligne de traitement donnait un taux de RO de 72 % dont la moitié en état de RC. Avec une durée moyenne de durée de la réponse de 14 mois (6 à 28).…”
Section: Autres Cytotoxiques : Cisplatine éToposide Estramustineunclassified
“…Cependant, quelques études ont montré une efficacité notable en première ligne de traitement, parfois supérieure aux traitements de référence. Ainsi, dans une étude publiée en 1985 [10], il était montré que l'association CDDP/Doxo/CPM chez des patientes métastatiques en 1 re ligne de traitement donnait un taux de RO de 72 % dont la moitié en état de RC. Avec une durée moyenne de durée de la réponse de 14 mois (6 à 28).…”
Section: Autres Cytotoxiques : Cisplatine éToposide Estramustineunclassified
“…Phase II studies of CDDP alone in pretreated patients have shown conflicting results: some authors failed to demonstrate activity of CDDP therapy [1], while others observed a response rate ranging from 12 to 20% [2][3][4]. More interesting results were obtained in untreated patients, both with CDDP alone [5,6], and in combination therapy [7].…”
Section: Introductionmentioning
confidence: 99%